2023
DOI: 10.3390/ijerph20042924
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Domestic Refrigerator Storage Temperatures in Poland for Use as a QMRA Tool for Exposure Assessment

Abstract: In the framework of Quantitative Microbiological Risk Assessment, the estimation of the ingested dose of a hazard by the consumer is of paramount importance. This may be calculated by means of predictive modeling of growth/inactivation of the pathogen studied. For products that spend the majority of their shelf life in the domestic refrigerator, storage temperature will significantly impact the microbial population dynamics. To describe the variability of domestic storage temperatures in Poland, a survey inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The most obvious safety risks are related to storage, complying with sickness rules, and personal hygiene (Chapters 4 & 5). We found that in these FSEs, raw ingredients are not always immediately stored upon arrival and are sometimes exposed to unfavourable conditions, which can increase the likelihood of temperature abuse and contamination, and raise the risk of foodborne illnesses (Stefanou et al, 2023). On the other hand, in Saudi Arabia, Indonesia, and Malaysia certain families opt to directly use the ingredients as it is common to procure fresh ingredients and promptly prepare and cook them to retain the genuine flavours (Abuqurayn, 2019).…”
Section: Food Safety Risks For Heritage Food Productionmentioning
confidence: 99%
“…The most obvious safety risks are related to storage, complying with sickness rules, and personal hygiene (Chapters 4 & 5). We found that in these FSEs, raw ingredients are not always immediately stored upon arrival and are sometimes exposed to unfavourable conditions, which can increase the likelihood of temperature abuse and contamination, and raise the risk of foodborne illnesses (Stefanou et al, 2023). On the other hand, in Saudi Arabia, Indonesia, and Malaysia certain families opt to directly use the ingredients as it is common to procure fresh ingredients and promptly prepare and cook them to retain the genuine flavours (Abuqurayn, 2019).…”
Section: Food Safety Risks For Heritage Food Productionmentioning
confidence: 99%